Investigating the mechanism of recognition and structural dynamics of nucleoprotein-RNA complex from Peste des petits ruminants virus via Gaussian accelerated molecular dynamics simulations. Issue 5 (24th March 2022) - Roy, Rajarshi; Mishra, Anurag; Poddar, Sayan; Nayak, Debasis; Kar, Parimal
Abstract: The nucleocapsid (N) protein from Peste des petits ruminants virus enwraps the nascent genomic RNA primarily to protect it from cellular enzymatic degradation. Here, we have combined molecular modeling and 1 μ s long Gaussian accelerated molecular dynamics simulations to study the structural and conformational properties of the apo N-protein and three protein-RNA complexes, namely wild type (WT), MT1 (I46T/E297D/G342E), and MT2 (I46T/E297D/G342E/W333G). The root-mean-squared deviation (RMSD) analysis reveals that although MT2 deviates most significantly from the initial structure, the RNA binding region is more stable compared to WT or MT1. Further, the flexible nature of the N protein is revealed from the principal component analysis. Our study shows that the solvent accessible surface area of the binding region increases drastically for both mutant complexes compared to WT. The dynamic cross-correlation analysis suggests that the overall anticorrelated motion weakens after the RNA binding. MT2 displays a relatively larger positive correlation than WT or MT1. The binding free energy is estimated for all three complexes via the molecular mechanics/generalized Born surface (MM/GBSA) scheme, and it decreases in the order WT > MT1 > MT2. In all cases, the protein-RNA binding is mainly driven by the van der Waals interactions since the intermolecular electrostatic interaction is overcompensated by desolvation energy. All hotspot residues are identified from the per-residue decomposition of the total binding free energy. In MT2, RNA contributes most favorably compared to WT or MT1. We believe our study will help in understanding the mechanism of RNA recognition by N proteins. Communicated by Ramaswamy H. Sarma